Multiple memories can be simultaneously reactivated during sleep as effectively as a single memory - Eitan Schechtman (Nature Portfolio, 2021)
Schechtman et al. examine whether the effect of cued reactivation during sleep on memory depends on the amount of information being reactivated via cues during sleep. Their results show that multiple memories can be consolidated in parallel, suggesting brain capacity for reactivation is not limited by separate resources needed for individual memories.